The Relationship Between Balanced Nutrition Knowledge and Food Choices Through Online Food Delivery Applications Among Students of Universitas Muhammadiyah Surakarta - Annisa Nur Hanifah; Firmansyah; Siti Zulaekah (JURNAL KESMAS DAN GIZI (JKG), 2025)
The development of digital technology has a significant role in transforming societal patterns in fulfilling food needs, including the emergence of online food delivery applications that are increasingly popular among university students. Various factors influence food choice decisions, one of which is the level of nutritional knowledge that is expected to encourage healthy and balanced eating behavior. The study aimed to determine the relationship between balanced nutrition knowledge and food choices made through online food delivery applications among students of Universitas Muhammadiyah Surakarta. The research employed a quantitative approach with a cross-sectional design, involving 108 respondents selected using a purposive sampling technique. Data on balanced nutrition knowledge and food choices were collected using a questionnaire that had been tested for validity and reliability. The results of the study show that most respondents have a low level of nutrition knowledge (76,9%) and tend choose foods that are not nutritionally balanced (93,5%). No significant relationship is found between balanced nutrition knowledge and food choices made through online food delivery applications (p=0,725). The findings of this study highlight the importance of improving nutrition literacy and developing balanced eating habits so that students not only possess nutritional knowledge but also are able to apply it in making healthy food choices through online food delivery applications